Experimental study on drag characteristics of the practical rigid net under different current conditions - Yu, Songchen; Qin, Hongde; Li, Peng; Gong, Fangyu; Tian, Yu (Frontiers in Marine Science, 2023)
The net structure of a cage is an important component to ensure the survival environment of aquaculture. In order to ensure the safety of the net, an experimental study on practical rigid nets is conducted in this paper. The drag force characteristics of the nets with different mesh sizes and different twine thicknesses are analyzed, and the impact of 90° and 45° attack angles on the drag force characteristics of the net are further studied. The empirical formulae for calculating the drag force of the net under different attack angles are given. The calculated drag forces are compared with the literature, and the results are in good agreement. Particularly, the current velocity is taken as one of the variables in the formulae to include the influence of nonlinear factors caused by the extreme current velocity in the drag force calculation.